ANALYSIS OF THE EPIDEMIOLOGICAL PROFILE OF PATIENTS DIAGNOSED WITH LEPROSY IN THE SOUTH REGION OF BRAZIL IN THE YEARS 2012 TO 2022 (REMUNOM, 2024)
Leprosy is an infectious-contagious pathology whose etiological agent is Mycobaterium leprae. Its existence dates back to ancient times and throughout history it has been mentioned in sacred texts of different religions, and is still common today. In relation, its pathophysiology is evident in the skin and peripheral nerves, causing chronic neuropathies that may be associated with deformities and disabilities. It is important to highlight that Brazil ranks second in the identification of new cases, even with the decrease in the incidence rate of this disease over the last decade. Leprosy is mainly characterized by being linked to unfavorable social contexts, simultaneously economic and geographical conditions, it is known that the Brazilian regions most affected are those with the most precarious conditions. This study is an epidemiological profile of patients diagnosed with leprosy in the southern region of Brazil. This is a documentary study and data collection is through DATASUS/Tabnet.